A novel mutation of the glycyl-tRNA synthetase (GARS) gene associated with Charcot–Marie–Tooth type 2D in a Chinese family. (September 2015) - Sun, Aping; Liu, Xiangyi; Zheng, Mei; Sun, Qingli; Huang, Yu; Fan, Dongsheng
<x content-type="archive" xml:space="preserve">Abstract</x> Objective: To explore the clinical features of a novel glycyl-tRNA synthetase (GARS) gene mutation in a family with Charcot–Marie–Tooth disease type 2D (CMT2D). Methods: Exome capture with the next-generation sequencing technique was used to detect gene mutations. The mutations were verified by the polymerase chain reaction-single strand conformation polymorphism (PCR-SSCP) technique combined with DNA sequencing. Results: In this pedigree, eight members were affected; seven males and one female. The affected members initially manifested with the onset of hand muscle weakness and atrophy in adolescence followed by gradual development of distal lower limb involvement and minor sensory involvement. Electrophysiological studies revealed that this disease mainly involves axonal damage. Genetic detection showed that all affected family members had a heterozygous missense mutation, c.999G>T (p.E333D), of the GARS gene. Conclusions: The c.999G>T mutation is a novel mutation of the GARS gene that has not been previously reported. The phenotype of this family is CMT2D, which is first reported in Chinese population.